2022
DOI: 10.1007/s11676-022-01485-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of ACBP gene family in Populus reveal salinity alkali-responsive profiles

Abstract: Acyl-CoA-binding proteins (ACBPs) are important for the transport of acyl groups for macromolecular biosynthesis involved in plant growth, development, and diverse stress (e.g., cold, drought, salinity, and heavy metals) responses. Here, we report the phylogeny and characteristics of the ACBP family in the woody plant Populus trichocarpa. Eight genes encoding ACBP proteins were identified, and they are distributed on eight chromosomes in P. trichocarpa. These PtACBP genes were divided into four subgroups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The WD40 related proteins are involved in plant resistance to alkali stress 84 . The genes encoding ankyrin repeat domain has been reported to be associated with salinity-alkali stresses 85 . Our results showed that the LD distance within the alfalfa populations with long-term grazing history was larger (r 2 reduced to 0.2 after 3 cM) than previous studies 24 , 86 , 87 .…”
Section: Discussionmentioning
confidence: 99%
“…The WD40 related proteins are involved in plant resistance to alkali stress 84 . The genes encoding ankyrin repeat domain has been reported to be associated with salinity-alkali stresses 85 . Our results showed that the LD distance within the alfalfa populations with long-term grazing history was larger (r 2 reduced to 0.2 after 3 cM) than previous studies 24 , 86 , 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that titanium promotes growth stimulation and facilitates the absorption of crucial elements like calcium, nitrogen, magnesium, manganese, phosphorus, iron, and zinc [ 13 ]. These intracellular alterations initiate diverse signaling pathways to translate physical stress into an appropriate biochemical response, each impacting the expression of stress-responsive genes [ 14 ]. The activation of these pathways facilitates plant adaptation and enhances its resilience against stressors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%